KARYA KEMALEDIZINE SEBAGAI REPRESENTASI KRITIK KEBERAGAMAAN MASYARAKAT ISLAM INDONESIA DALAM MEDAN SENI RUPA KONTEMPORER INDONESIA - Khairi, Miftahul; Arisman, Willy (ARTCHIVE: Indonesian Journal of Visual Arts and Design, 2023)
Artistic expression is a manifestation of cultural phenomena specific to an era and region. That is evident in Islamic visual arts, which present innovative forms with contemporary content. This research focuses on the works of Kemalezedine, who, through the lens of iconography and sociology of art theories, reveals religious and social criticism in the context of the Indonesian Muslim community. His works intensely highlight and criticize the phenomenon of Arabism, often appearing in understanding, spiritual practices, and identity politics in Indonesia. Criticism and discourse exploration in the creation of Kemalezedine's works are closely related to his creative process, formed while participating in the Neo Pitamaha and NU Abstract communities. His "Bloodline series" (2019) marks the pinnacle of religious criticism among the Indonesian Muslim community, especially the fundamentalists. This work questions the laws of symbolic depiction in Islamic visual arts and also sheds light on socio-cultural and identity politics issues rooted in Indonesia. With a critical and analytical approach, Kemalezedine's work serves not only as a medium of artistic expression but also as a deep social reflection medium, reflecting the dynamics and challenges faced by the contemporary Muslim community in Indonesia.